2020
DOI: 10.48550/arxiv.2012.03593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Algebraic geometry of discrete interventional models

Abstract: We investigate the algebra and geometry of general interventions in discrete DAG models. To this end, we develop the formalism to study these models as subvarieties of multiprojective space and introduce a theory for modeling soft interventions in the more general family of staged tree models. We then consider the problem of finding their defining equations, and we derive a combinatorial criterion for identifying interventional staged tree models for which the defining ideal is toric. This criterion, when comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A result similar in spirit to Proposition 2 was derived in Duarte and Solus (2020) formalizing the equivalence between decomposable BNs and balanced staged trees, which are characterized by a polynomial condition based on interpolating polynomials (Görgen et al, 2015), holding for all simple staged trees. Görgen et al (2020) demonstrated that balanced staged trees, and thus also simple ones, are regular exponential families.…”
Section: Simple Staged Treesmentioning
confidence: 83%
“…A result similar in spirit to Proposition 2 was derived in Duarte and Solus (2020) formalizing the equivalence between decomposable BNs and balanced staged trees, which are characterized by a polynomial condition based on interpolating polynomials (Görgen et al, 2015), holding for all simple staged trees. Görgen et al (2020) demonstrated that balanced staged trees, and thus also simple ones, are regular exponential families.…”
Section: Simple Staged Treesmentioning
confidence: 83%
“…As demonstrated by Smith and Anderson (2008) and Duarte and Solus (2020), every BN can be represented as a staged tree. However, the class of staged tree models is much more general and can represent not only symmetric, but also context-specific, partial and local independences, using the terminology of Pensar et al (2016).…”
Section: Introductionmentioning
confidence: 99%